Perception Study of Consumers about Online Purchase through Digital Financing - Milan Tah; Dr. Puspalata Mahapatra (International Journal of Engineering and Management Research, 2023)
This article aims to explore the relationship between digital finance and online buying, the benefits of online buying and the satisfaction of customers when they buy products online. The study is based on both primary and secondary data. The primary data was collected through structured questionnaire prepared using google forms and circulated among respondents through online whatsapp groups. The random sampling method is employed for the study. 114 respondents answered the questions and based upon their views analysis of the study has been made. The secondary data were collected from published reports, journals, conference proceedings and books to have clear knowledge of the concepts and previous studies made on online buying and digital finance and to find the gap. Through literature review it was observed that many researchers either focus only on digital finance or on online buying. But very few researchers made the study both on digital finance and online buying. So here in this study we tried to make a conceptual study of both online buying and digital finance and the perception of people about both of them. The findings of the study shows that digital finance makes it easier for the people to access financial services at anytime and from anywhere as these are available at their finger tip through their mobile phones. Many respondents are of the opinion that internet is the measure source to know about online buying of products and services and cheap data plans help to have access to internet. The study shows online buying is easier for people as it has many benefits to offer but the measure force is digital payments as it helps in making the cumbersome process of making payments for the purchases simple i.e at a click.